Labor Market Effects of US Sick Pay Mandates - Stefan Pichler; Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2016)
This paper exploits temporal and spatial variation in the implementation of US sick pay mandates to assess their labor market consequences. We use the Synthetic Control Group Method (SCGM) and the Quarterly Census of Employment and Wages (QCEW) to estimate the causal effect of mandated sick leave on employment and wages. Our findings do not provide much evidence that employment or wages were significantly affected by the mandates which typically allow employees to earn one hour of paid sick leave per work week, up to seven days per year. Joint tests for all treatment regions let us exclude, with 90% statistical probability, that wages decreased by more than 1% as a result of the mandates. With 92% probability, we can exclude that employment decreased by more than 1%.
Keywords: I12; I13; I18; J22; J28; J32; 330; sick pay mandates; sick leave; medical leave; employer mandates; employment; wages; synthetic control group; United States; Quarterly Census of Employment and Wages (QCEW)